MiR-26a-5p Suppresses Wnt/β-Catenin Signaling Pathway by Inhibiting DNMT3A-Mediated SFRP1 Methylation and Inhibits Cancer Stem Cell-Like Properties of NSCLC. (11th July 2022) - Yu, Jie; Ge, Zhe; Chen, Shunqiong; Li, Shaoying; Zhang, Xin; Hu, Jie; Guo, Wei; Wang, Yan
Abstract : Background . Lung cancer is a malignant cancer which results in the most cancer incidence and mortality worldwide. There is increasing evidence that the pattern of DNA methylation affects tumorigenesis and progression. However, the molecules and mechanisms regulating DNA methylation remain unclear. Methods . The expression of miR-26a-5p in NSCLC cell lines was detected by qPCR and verified in NSCLC tissues from TCGA using Limma R package. CCK-8 assay, plate clone formation assay, flow cytometry, and sphere formation assay were used to detect the cell proliferation, colony formation, cell cycle, and cancer stem cell- (CSC-) like property in NSCLC cell lines. The immunoblotting was used to detect the protein levels of DNMT3A, SFRP1, and Ki67. Global DNA methylation levels and DNA methylation levels of SFRP1 promoter were examined using ELISA and MSP-PCR assay, respectively. The distribution of β -catenin was examined using immunofluorescence (IF). Besides, xenograft mouse model was used to investigate the antitumor effects of miR-26a-5p in vivo. The pathology and protein levels were, respectively, detected by hematoxylin and eosin (H&E) and immunocytochemistry (IHC). Results . The expression of miR-26a-5p was downregulated in the tumor tissues comparted to adjacent normal tissues as well as NSCLC cell lines compared to normal lung epithelial cell (BEAS2B). The overexpression of miR-26a-5p inhibited cell proliferation, colony formation, CSC-like property, and arrested cell cycle at G1 phase. DNMT3A was a target of miR-26a-5p and upregulated DNA methylation on SFRP1 promoter. Mechanistically, miR-26a-5p repressed cell proliferation, colony formation, CSC-like property, and arrested cell cycle at G1 phase by binding DNMT3A to reduce DNA methylation levels of SFRP1 then upregulated SFRP1 expression. Moreover, miR-26a-5p exerted antitumor effects in vivo . Conclusion . Our results revealed that miR-26a-5p acted as a tumor suppressor through targeting DNMT3A to upregulate SFRP1 via reducing DNMT3A-dependent DNA methylation.